New Approaches in Foundation Engineering 2022
DOI: 10.5772/intechopen.102802
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Glass Fiber Reinforced Clayey Soil for Its Possible Application as Pavement Subgrade Material

Abstract: A clayey soil reinforced with commercially obtainable20 mm glass fiber of varying fiber content (fc = 0.25 to 1% by soil dry weight) was investigated in lab for its possible application as road pavement material. Standard proctor compaction, unconfined compression strength (UCS), California Bearing Ratio (CBR) and undrained triaxial compression tests were conduction on compacted soil-fiber specimens as per ASTM standard. From the fiber mixing process it has been observed that fiber can be uniformly mixed into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
(55 reference statements)
1
1
0
Order By: Relevance
“…This indicates a change in consistency after the addition of sand and an improvement in soil workability. Several studies have also shown the same trend [5,7].…”
Section: A Atterberg Limit Test Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…This indicates a change in consistency after the addition of sand and an improvement in soil workability. Several studies have also shown the same trend [5,7].…”
Section: A Atterberg Limit Test Resultssupporting
confidence: 57%
“…Several studies have been conducted on the phenomena related to this type of soil. The soil treatment techniques vary according to their character, such as the treatment by adding rubber fiber [3], natural or produced and product materials [4][5][6], and the use of waste tires, ashes and sewage sludge, which have shown good potential for soil stabilization [7].…”
Section: Introductionmentioning
confidence: 99%